Intramuscular Hemangioma of the sternocleidomastoid muscle: A Rare Unusual Neck Mass - Sigdel, Brihaspati; Maharjhan, Rajesh; Dubey, Tulika; Neupane, Bhima (Journal of Gandaki Medical College-Nepal, 2020)
Hemangiomas of the head and neck region comprise about 60 to 70% of all benign tumors. Intramuscular hemangioma is a rare, slow-growing, angiomatous tumor. We report a rare case of an Intramuscular Hemangioma of Right sternocleidomastoid muscle in a six years old girl presenting for four years and with extensive involvement necessitating excision. Microscopic excision reduces the risk of recurrence.